Fertility and Pregnancy Outcomes in Women with Polycystic Ovary Syndrome Following Bariatric Surgery - Benito, Estela; Gómez-Martin, Jesús M; Vega-Piñero, Belén; Priego, Pablo; Galindo, Julio; Escobar-Morreale, Héctor F; Botella-Carretero, José I (The journal of clinical endocrinology and metabolism, 2020)
Restoration of ovulation is quite common in women with polycystic ovary syndrome (PCOS) after surgically induced weight loss. Whether or not this results in an improvement of PCOS-associated infertility is uncertain. To study fertility and gestational outcomes in women with PCOS after bariatric surgery. Unicenter cohort study. Academic hospital. Two hundred and sixteen premenopausal women were screened for PCOS before bariatric surgery. Women were followed-up after the intervention until mid-2019 regardless of having or not PCOS. All participants underwent bariatric surgery from 2005 to 2015. Pregnancy and live birth rates in the PCOS and control groups. In women seeking fertility, pregnancy rates were 95.2% in PCOS and 76.9% in controls (P = 0.096) and live birth rates were 81.0% and 69.2%, respectively (P = 0.403). The time to achieve the first pregnancy after surgery was 34 ± 28 months in women with PCOS and 32 ± 25 months in controls. Albeit the mean birth weight was lower (P = 0.040) in newborns from women with PCOS (2763 ± 618 g) compared with those from controls (3155 ± 586 g), the number of newborns with low birth weight was similar in both groups (3 in the PCOS group and 1 in the controls, P = 0.137). Maternal (17.6% in PCOS and 22.2% in controls, P = 0.843) and neonatal (23.5% in PCOS and 14.8% in controls, P = 0.466) complications were rare, showing no differences between groups. Pregnancy and fertility rates in very obese women with PCOS after bariatric surgery were high, with few maternal and neonatal complications.